Experimental advances with the QICK (Quantum Instrumentation Control Kit) for superconducting quantum hardware - Ding, Chunyang (2024)
The Quantum Instrumentation Control Kit (QICK) is a standalone open-source qubit controller that was first introduced in 2022. In this follow-up work, we present recent upgrades to the QICK and the experimental use cases they uniquely enabled for superconducting qubit systems. These include multiplexed signal generation and readout, mixer-free readout, predistorted fast flux pulses, and phase-coherent pulses for parametric operations, including high-fidelity parametric entangling gates. We explain in detail how the QICK was used to enable these experiments.